Heralds of the historiography of History: disputes by a concept of historiography in the letters of Amaral Lapa sent the Nilo Odalia - Anhezini, Karina [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
This current article deals with the interpretation of a dispute about the definition of historiography in Brazil. To let it clearer, the main objective is to analyze the requirements formulated by Nilo Odalia (1929-2004) and Jose Roberto do Amaral Lapa (1929-2000), two university professors, who have dedicated themselves to define, in the 1970s and 1980s, study prospects for the Brazilian historiography. Both emphasized the importance of history as part of the historical discipline, Amaral Lapa craved to see it as an area of specialization that have appeared next to the Political History, Social, Economic and Cultural while Odalia projected think the historiographical fact from a epistemological reflection. The privileged sources in this study are the epistolary exchanges that make up Nilo Odalia Personal Archive, donated in 2012 to CEDAP (Documentation Centre and Research Support of the Sao Paulo State University) of UNESP - Assis.
Keywords: Nilo Odalia; Jose Roberto do Amaral Lapa; Cedap; Historiography